Hospital capacity and management preparedness for pandemic influenza in Victoria. (1st April 2014) - Dewar, Ben; Barr, Ian; Robinson, Priscilla
Abstract Objective: This study was designed to investigate acute hospital pandemic influenza preparedness in Victoria, Australia, particularly focussing on planning and management efforts. Methods: A prospective study was conducted by questionnaire and semi‐structured interview of health managers across the Victorian hospital system from July to October 2011. Participants with responsibility for emergency management, planning and operations were selected from every hospital in Victoria with an emergency department to complete a questionnaire (response rate 22/43 = 51%). Each respondent was invited to participate in a phone‐based semi‐structured interview (response rate 11/22 = 50%). Results: Rural/regional hospitals demonstrated higher levels of clinical (86%) and non‐clinical (86%) staff contingency planning than metropolitan hospitals (60% and 40% respectively). Pandemic plans were not being sufficiently tested in exercises or drills, which is likely to undermine their effectiveness. All respondents reported hand hygiene and standard precautions programs in place, although only one‐third (33%) of metropolitan respondents and no rural/regional respondents reported being able to meet patient needs with high levels of staff absenteeism. Almost half Victoria's healthcare workers were unvaccinated against influenza. Conclusions and implications: Hospitals across Victoria demonstrated different levels of influenza pandemic preparedness and planning. If a more severe influenza pandemic than that of 2009 arose, Victorian hospitals would struggle with workforce and infrastructure problems, particularly in rural/regional areas. Staff absenteeism threatens to undermine hospital pandemic responses. Various strategies, including education and communication, should be included with in‐service training to provide staff with confidence in their ability to work safely during a future pandemic.